The making of a video program ([Pasig, Metro Manila] Philippine Human Resource Development Center)
Shows the techniques of producing a quality video program.
Narrator/presentor, Debbie C. Quebral.
Keywords: Video recordings -- Production and direction; Mass communication; Technology